Effect of Replacement of Maize Grains by Phalaris minor Seeds in the Concentrate Mixture on Milk Production and Milk Fatty Acid Profile in Crossbred Cows - Kaur, Jasmine; Thakur, S. S.; Tyagi, A. K. (Indian Journal of Animal Nutrition, 2017)
This study was conducted to investigate the effect of feeding Phalaris minor seeds as an alternate energy source on milk yield, milk fat content and fatty acid profile of milk in crossbred cows. Eighteen lactating crossbred cows (Karan Fries) in their mid lactation were divided into 3 groups of 6 animals each on the basis of milk production and days in milk. The cows were fed as per requirement (NRC, 2001) for 120 days. Maize grains were replaced by P. minor seeds in the concentrate mixture at 0, 50 and 75% (DM basis) level in groups C, T1and T2, respectively. The predominant fatty acids in P. minor seeds were palmitic and oleic acids. FCM (4%) yield and milk fat content during 120 days experimental period was similar in all the groups. The fatty acid profile of milk of cows in groups T1 and T2 was similar to that of group C except that the level of trans-9-elaidic acid was lower (P<0.05) in groups T1 and T2 as compared to that in group C. Thus, P. minor seeds could safely replace maize grains up to 75% in the concentrate mixture of lactating crossbred cows without any adverse effect on milk yield, milk fat content or fatty acid composition of milk fat.